Design of a cylindrical LED substrate without radiator. (December 2017) - Tang, Fan; Guo, Zhenning
Abstract: To reduce the weight and production costs of light-emitting diode (LED) lamps, we applied the principle of the chimney effect to design a cylindrical LED substrate without a radiator. We built a 3D model by using Solidworks software and applied the flow simulation plug-in to conduct model simulation, thereby optimizing the heat source distribution and substrate thickness. The results indicate that the design achieved optimal cooling with a substrate with an upper extension length of 35 mm, a lower extension length of 8 mm, and a thickness of 1 mm. For a substrate of those dimensions, the highest LED chip temperature was 64.78 °C, the weight of the substrate was 35.09 g, and R jb = 7.00 K/W. If the substrate is powered at 8, 10, and 12 W, its temperature meets LED safety requirements. In physical tests, the highest temperature for a physical 8 W cylindrical LED substrate was 66 °C, which differed by only 1.22 °C from the simulation results, verifying the validity of the simulation. The designed cylindrical LED substrate can be used in high-power LED lamps that do not require radiators. This design is not only excellent for heat dissipation, but also for its low weight, low cost, and simplicity of manufacture.